Getting started with the internet of things. - Pfister, Cuno, ....- (Beijing : O'Reilly, 2011)
The Internet of Things is the new generation of devices that serve as the Internet's interface to the physical world. Today's tiny microcontrollers, sensors, and actuators are powerful, inexpensive, and simple enough to code that anyone with basic programming skills can create a variety of fun, useful, and even profitable systems -- such as devices that detect and extinguish fires or automatically water plants when the soil becomes too dry. This hands-on introductory guide will quickly show you how it's done. You'll learn how to program embedded devices using the .NET Micro Framework and the Netduino Plus board, and then connect these devices to the Internet using Pachube, a cloud platform for sharing real-time sensor data. Getting Started with the Internet of Things briefly introduces the tools and then walks you though several techniques for using them, using a series of C# examples: Develop programs that demonstrate the use of simple outputs (actuators) and inputs (sensors) Build client programs that show how measurements can be pushed to an existing Web service Create server programs that provide Web services to clients on the Web Develop a program that is both client and server and runs in the cloud Get .NET classes and methods needed to implement all of the book's examples